Review on critical liquid loading models and their application in deep unconventional gas reservoirs - He, Feng; Huang, Xusen; Yang, Yadong; Bu, Chengzhong; Xing, Hongchuan; Pu, Lingang; Zhang, Senlin (Frontiers in Energy Research, 2024)
The exploitation of deep unconventional gas resources has gradually become more significant attributing to its huge reserves and severe depletion of convention gas resources in the world. The proportion of deep unconventional gas reservoirs in the total gas resources cannot be underestimated, including shale gas, tight gas, gas of coal seam etc. Due to the low permeability and porosity, hydraulic fracturing technology is still an important means to develop deep unconventional gas resources. However, the presence of fracturing fluids and water will accumulate in the bottom of wellbore to significantly reduce gas production. The liquid loading model can be used to determine when the gas well begins to load the liquid. In this work, different types of liquid loading models are classified, and the applicability of different models is analyzed. At present, the existing critical liquid carrying models can be divided into mechanism models, semi-empirical models and mechanism models. The model established by Turner is a typical mechanism model. There are great differences in the application of critical liquid loading model between vertical and horizontal wells. The field cases of liquid loading model in different gas fields are provided and discussed. The mechanism of liquid loading models in recent years is introduced and analyzed. The physical simulations and experimental work therein are described and discussed to clarify the feasibility of the modeling mechanism. This article also presents the limitation and future work for improving the liquid loading models.